(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
In a developing country like India, social security provisions and measures have a two fold significance. Social security provisions constitute essential steps towards the aim of a welfare state by bringing improvements in the living standard and safeguarding people from uncertainties that may arrive in the future. The Human Resource Management department in companies is worried about the management of people at the workplace, and it is essential for them to secure the cooperation of workers and employees to increase productivity and to earn good profits. The productivity of employees will be high only if they are delighted with their employer and with the working environment at their workplace. Good and satisfactory social security provisions will make employees satisfied with their jobs and will improve their performance as well. Someone who feels safe and satisfied with their jobs gives good performance and improves the production at their job.A sample of 250 respondents was collected from respondents.